Local Soviet nomenclature of the BSSR of late Stalinism (1945–1953) - Elizarov, Sergey A. (Journal of the Belarusian State University. History, 2021)
The article examines the process of restoration and development of the nomenclature mechanism of personnel policy in the BSSR in the first post-war decade, which received the name «late Stalinism» in modern historiography. The main attention is paid to the leading employees of local government bodies – the executive committees of the Soviets of Working People’s Deputies. The article describes the main trends in the transformation of the organisation of nomenclature practice – centralisation and decentralisation. The main hierarchical levels of nomenclatures are highlighted (from the Central Committee of the all-Union Communist Party(b) – the CPSU to the district and city committees of the CP(b)B – CPB), their specific content is shown in the time dynamics. It is noted that the existing hierarchy of nomenclature positions in many respects more accurately than their official administrative status determined the real position of an employee in the structure of power and management. Initially the high level of renewal of the composition of the chairmen of local executive committees was replaced in the early 1950s by its relative stabilisation. They tried to appoint Communists with pre-war experience who had already been tested in various leadership positions to senior positions in the local structures of the state administration apparatus. The level of education played a role only at the district and city levels of the local administrative hierarchy, for its highest level – the chairmen of regional executive committees – the main importance was still the experience of leadership work. The work experience in the positions held and the general experience of managerial work increased somewhat, the level of education of the chairmen of district and city executive committees increased, which made it possible to move to a higher level of requirements in the selection of personnel (the availability of specialised higher, technical or agricultural, education).
Keywords: Belarusian SSR; late Stalinism; personnel policy; nomenclature; Communist Party; party committees; executive committees; Soviets of Working People’s Deputies; government and management bodies